Stress Effects on Soil Freezing Characteristic Curve: Equipment Development and Experimental Results - Mu, Q.Y. (2020)
The soil freezing characteristic curve (SFCC) defines the relationship between soil temperature and unfrozen water content. This curve is important for predicting water flow and heat conduction in frozen soils, as well as freezing heave and thawing settlement. So far, SFCCs reported in the literature were usually determined at zero stress. To investigate stress effects on SFCC, a stress‐ and temperature‐controlled triaxial apparatus was developed in this study. The unfrozen volumetric water content was measured using a newly developed noninvasive time domain reflectometry (TDR) probe. The new apparatus was used to measure SFCCs of two typical soils (i.e., clay and sand) at different stress conditions (i.e., 30, 100, and 200 kPa). Each specimen was subjected to compression, and then a cycle of freezing and thawing. As expected, for both soils, the saturated water content prior to freezing was smaller at higher stresses because of compression. During the subsequent freezing and thawing, the soil specimen at a higher stress was able to retain more liquid water than that at a lower stress. The higher unfrozen water retention capacity at higher stresses is mainly because the pore size of a soil specimen becomes smaller during compression. Hence, more water can retain a liquid state due to the enhanced capillarity. On the other hand, stress effects on the SFCC were found to be more significant for clay than for sand. This is likely because the stress‐induced change in pore size distribution is larger in clay due to its higher compressibility.